PENGARUH TERAPI TERTAWA TERHADAP STRES PSIKOLOGIS PADA LANJUT USIA DI PANTI WERDHA KOTA MANADO (JURNAL KEPERAWATAN, 2015)
Abstract: The increase in the number of elderly living certainly have more impact to the occurrence of diseases in the elderly. Elderly will experience a variety of physical problems, mental, social, economic, and psychological. One of the psychological issues that may be experienced by the elderly are stressed. One type of therapy that can induce relaxation to reduce the stress that laughter therapy. The purpose of this study was to determine the therapeutic effect of laughter on psychological stress in the elderly in Nursing Elderly Manado. The design of this research was experimental with One Group Pre-Test -Post-Test Design. The sampling technique was performed with total sampling with a sample of 37 peoples. Test results using Paired Samples T-Test obtained p value = 0.000